2012
DOI: 10.1143/apex.5.051301
|View full text |Cite
|
Sign up to set email alerts
|

Schottky Source/Drain Ge Metal–Oxide–Semiconductor Field-Effect Transistors with Directly Contacted TiN/Ge and HfGe/Ge Structures

Abstract: Metal/Ge contacts with high Schottky barrier heights on p- and n-Ge substrates could be formed using direct sputter depositions from TiN and Hf, respectively. The barrier heights were 0.53 and 0.60 eV for the p- and n-Ge substrates, respectively, which are available to source/drains (S/Ds) in Schottky n- and p-channel metal–oxide–semiconductor field-effect transistors (MOSFETs). We fabricated the n- and p-MOSFETs and demonstrated their operation. In particular, the n-MOSFET operation is the first demonstration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…Yamamoto et al have recently demonstrated metal source=drain n-and p-MOSFETs using TiN contact. 187) As discussed in Sect. 6.1, several methods have been reported to enable the metal contact to the n-Ge substrate ohmic.…”
Section: Metal Source/drain Fetmentioning
confidence: 96%
“…Yamamoto et al have recently demonstrated metal source=drain n-and p-MOSFETs using TiN contact. 187) As discussed in Sect. 6.1, several methods have been reported to enable the metal contact to the n-Ge substrate ohmic.…”
Section: Metal Source/drain Fetmentioning
confidence: 96%
“…Using this contact technique, we demonstrated p-MOSFET operations. 10,11) However, there were two drawbacks of the use of the HfGe=Ge contact. 12) The first one is that the HfGe film was prone to oxidation during processing.…”
mentioning
confidence: 99%
“…[231][232][233] Recent intensive studies on controlling and reducing the SBH against n-Ge as well as doping technologies of high concentration donors into Ge are expected to lead to further reduction in the S=D parasitic resistance of Ge n-MOSFETs. 39,[234][235][236][237][238][239][240][241]…”
Section: Cmos Devices Using Ge/iii-v Materialsmentioning
confidence: 99%